Numerical study of circle fractal grid perforated plate as a turbulent generator in combustion chamber - Mohd Fahmi, Mohd Fahmi; Manshoor, Bukhari; Khalid, Amir; Mohd Al-Hafiz, Mohd Al-Hafiz (2013)
Fractal grids can be used to design turbulent flows with low power losses and high turbulence intensities for intense yet economic mixing over a region of designed length and location. The introducing circle grid perforated plate is the main aim of this present paper. In this numerical work, we want to ascertain a new approach in turbulence generators on the structure of premixes flames using perforated plate fractal-grids pattern. In this paper, we compared circle grid perforated plate by varies using its diameters, spacing and number of holes on the plate. The result showed good perceptivity of the fractal generated turbulence and the fractal flow physics. The turbulent intensity can be increased by a grid with higher blockage ratio.